Humorous Content on Social Media:Political Education against Money Politics in General Elections - Hidayaturrahman, Mohammad; Ubaid, Ahmad Hasan; Muchlashin, Anif (Reflection Journal, 2026)
Efforts to prevent money politics in Indonesian elections have failed miserably. The enactment of Law Number 7 of 2017 concerning Elections, which imposes criminal sanctions and fines on perpetrators, has failed to eradicate money politics. The Election Supervisory Agency (Bawaslu) has also failed to punish perpetrators of money politics. This study was conducted to determine the political education provided by netizens in combating money politics in Indonesia. This study used digital research methods to collect data on content created by netizens on YouTube, X, and TikTok. Data analysis using content analysis techniques. The study results revealed that political education provided by netizens to counter money politics on social media was delivered in three forms of humorous content. First, netizens urged legislative candidates not to give money to prospective voters, and also urged prospective voters not to accept money from legislative candidates. Second, they urged prospective voters to reject money politics offered by legislative candidates. Third, they warned prospective voters not to vote for legislative candidates involved in money politics. The novelty of this study lies in the finding that political education in the digital era is not only carried out by political parties, religious mass organizations, or public figures, but also by netizens, as a form of concern about bad political practices in general elections.  Practically, this study has implications for the importance of strengthening anti-money laundering messages by Bawaslu and the General Elections Commission (KPU) on social media, not only through conventional media such as banners and billboards